Islam dan Budaya Masyarakat Gayo, Provinsi Aceh: Kajian Sejarah dan Sosial - Arfiansyah (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
This article argues that Gayonese community practice Islam through the culture and less concern with religious texts. Although the wave of islamization since the colonial time and post-independence was high, the process does not succeed in introducing what the local scholars called as Islamic tradition. Such situation forces the following ulama to defend culture by finding justification for every practice instead of abolishing it. There are two factors leading to the situation. First, ulama of colonial and post-colonial time did not succeed in finding what they called as Islamic tradition replacing the existing tradition. second, lacking of regeneration of reformer Ulama that drive the living reformer ulama to support culture by inserting Islamic values and norms into the culture. This effort is crucial as the Gayonese refers more to the culture than the religious texts. This Article historically studies the development of Islam in Gayonese community. It frames its historical analysis from the Dutch colonial period to post independence of Indonesia Republic. It generally observes the impact of islamization in the past to the current situation. This article brings back the fundamental question in socio-anthropological studies about Islam that why do Muslim who refer to same source of text understand and practice Islam in widely various expression. The question is applied to this research exploring the development of Islam in Gayonese community inhabiting Central Aceh and Bener Meriah District. Thus, this research questions how did Islam develop in colonial time and its impact to the local culture? did there a debate about religion and culture take place during the colonial time and post-independence of Indonesia? How does the past event affect the current practice of Islam in Gayonese community? the questions are explored historically by collecting relevant literatures and collective memory of the local people. The collective memory data were collected from 2015 to 2019.